2019
DOI: 10.1001/jamanetworkopen.2019.12565
|View full text |Cite
|
Sign up to set email alerts
|

Association of Histologic Disease Activity With Progression of Nonalcoholic Fatty Liver Disease

Abstract: IMPORTANCE The histologic evolution of the full spectrum of nonalcoholic fatty liver disease (NAFLD) and factors associated with progression or regression remain to be definitively established. OBJECTIVE To evaluate the histologic evolution of NAFLD and the factors associated with changes in disease severity over time. DESIGN, SETTING, AND PARTICIPANTS A prospective cohort substudy from the Nonalcoholic Steatohepatitis Clinical Research Network (NASH CRN) NAFLD Database study, a noninterventional registry, was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
234
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(246 citation statements)
references
References 29 publications
6
234
2
4
Order By: Relevance
“…A simple proposal based exclusively on elevated AST in type 2 diabetics would be easy to implement and have acceptable diagnostic properties despite sending “only” 25% to liver specialists. Recent publications have also found AST to be a simple marker for fibrosis 44 and that there is an association with progression of fatty liver disease 45 .…”
Section: Discussionmentioning
confidence: 99%
“…A simple proposal based exclusively on elevated AST in type 2 diabetics would be easy to implement and have acceptable diagnostic properties despite sending “only” 25% to liver specialists. Recent publications have also found AST to be a simple marker for fibrosis 44 and that there is an association with progression of fatty liver disease 45 .…”
Section: Discussionmentioning
confidence: 99%
“…NASH can regress without specific pharmacologic intervention; for example, weight loss through lifestyle modification improved NAFLD activity scores [49,50]. On the other hand, chronic inflammation induced by persistent HCV infection drives a maladaptive reparative reaction and over stimulates liver cell death and regeneration, promoting liver fibrosis and carcinogenesis [51].…”
Section: Discussionmentioning
confidence: 99%
“…This approach can be combined with serum-based markers of liver scarring to further increase the accuracy in diagnosing liver fibrosis [31]. Indeed, the exact quantification of liver scarring represents the central point in diagnosing patients with NAFLD since numerous studies have shown that fibrosis represents the limiting factor in patient survival [32,33]. Diagnosis of steatohepatitis in patients is based on histopathological evaluation of liver biopsies showing characteristic morphological features: macrovesicular steatosis, ballooned hepatocytes with cytoplasmic inclusions (Mallory-Denk bodies (MDBs)) and lobular inflammation.…”
Section: Diagnosismentioning
confidence: 99%